Assessing the Impact of Innovative Technologies on the Life Satisfaction of Older Adults in Russia and Vietnam; Changing Societies & Personalities; Vol. 7. iss. 3 - Barysheva G. A. Galina Anzelmovna; Klemasheva E. I. Elena Igorevna; Kashapova E. R. Elmira Ramisovna; Nguyen Thang Chien; Tran Ngoc Thi Bich (2023, 2023)
Заглавие с экрана